An Analysis of Water Security under Climate Change - Federica Cappelli (Fondazione Eni Enrico Mattei (FEEM), 2017)
Water is a multidimensional issue, involving water availability, access to freshwater, spatial and temporal distribution of resources, competition among its uses, ecosystems conservation, climate-related disasters and risks and several other aspects. The water security approach manages such complexity and proposes a comprehensive view of human security in relation to the water-related issues. Consequently, the solutions developed in order to face this multi-faceted concept should reflect its thorough vision. The aim of the present work is to investigate the relationship between climate change and water security. Exploring such a relationship is truly important in order to help policy-makers in the development of adaptation and mitigation strategies. In the water context, this challenge is further complicated by the possible conflicts arising between climate and water policies. In order to carry out such an analysis, an indicator measuring water security, namely the Water Security Index, is created. In the present work, climate change is considered from four different perspectives but, as revealed by the econometric results, it always has a predominant (negative) effect on water security.
Keywords: Q25; Q53; Q54; O13; 330; Water Security; Climate Change; Water Security Index; Econometrics; Maps